The Position of Ulayat Rights in Land Provision in the Implementation of National Development Viewed from the Perspective of Positive Law and Islamic Law - Qinayya, Syavira Alzena; Lusyany, Devi; Ika , Kharisma; Nirmalatifa , Febriana Ayu; Putri , ⁠Rizki Cahya Kusuma Riyanto (PT FORMOSA CENDEKIA GLOBAL, 2024)
Customary rights often face problems when connected with national development due to the legal status of customary land. In connection this matter, research is needed in order to understand the position of customary land in relation to national development. of customary land when it is connected with national development. In order to to examine this, the research in this case uses normative juridical research because an in-depth understanding is needed with regard to regulations that discuss regarding customary rights. The result of this research is the position of of customary rights in land acquisition in the context of national development is still very weak, which is due to the absence of regulation on customary rights. very weak, which is due to the absence of a more detailed regulation of customary rights. so that the customary rights community lacks supporting evidence and legality to obtain compensation. supporting evidence and legality to obtain compensation for the utilisation of customary rights for national development. for national development.